Memahami Konsep Manajemen BK Dengan Melihat Pola Organisasinya Di Sekolah - Bakhrudin All Habsy; Laura Maulita Agustin; Dira Anindia Ayu Rosidin; Tabita Tindie Yuliana; Pribadi Wahyu Santiko; Talitha Hasnabila Firjatullah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
The concept of management in guidance and counseling is the process of planning, designing, organizing, and directing in the process of providing guidance and counseling services in a school or an organization. The method used in this research is the literature study method, which is a written summary that includes articles from journals, books, and other documents that define theories and provide information. The results of this study include: (1) the concept of management in counseling guidance, (2) the principles of applying guidance and counseling management, (3) organizational patterns in guidance and counseling, (4) stages of applying management in guidance and counseling, and (5) forms of evaluation in the process of guidance and counseling services.